Control approaches for operating point stabilization of microring resonator modulators under fast perturbations - Cherian, Athira Jess; Michalka, Andreas; Murray, Kyle; Roell, Georg; Graichen, Knut (Proceedings Silicon Photonics XIX, 2024)

Full Physical Layer Simulation Tool to Design Future 77 GHz JCRS-Applications - Lübke, Maximilian; Su, Yanpeng; Cherian, Athira Jess; Fuchs, Jonas; Dubey, Anand; Weigel, Robert; Franchi, Norman (IEEE Access, 2022)
Vehicular communication systems get more and more attention with the upcoming fifth and sixth generation. Hereby, the focus lies on the development of the co-design or co-existence of communications and sensing. So called joints communications and radar sensing systems are seen as one key technology of 6G. As joint systems will have shared waveforms and hardware platforms, there is a huge benefit in cost and space which is one essential argument for the automotive industry. However, to design such a system for new applications like platooning or intersection assistance a physical layer has to be set up to represent the real physical layer properly. The proposed system design closes the lack of such a simulation tool and allows for full physical layer simulations, including e. g. the hardware non-idealities and the channel model for 77 GHz. The whole signal processing chain of the physical layer is built up and will be integrated in the higher layer state-of-the-art simulation frameworks like Veins or Artery in the next step. The communications design is developed in Simulink, whereas the sensing part is discussed. The proposed communications architecture covers several transmission approaches (serial, parallel), a CDMA based spreading, a radio frequency representation, the channel (simulated in a 3D-Ray-Tracing-tool) and the receiver structure (e. g. the synchronisation or the channel estimation). Several design criteria are discussed, like the serial or parallel design architecture, the maximum ratio combining or the phase and frequency compensation method. The whole system architecture is freely available (https://doi.org/10.5281/zenodo.6482565) and in consequence, the different signal blocks and parameters can be enabled or disabled for evaluations according to future design criteria requirements. <br